Pharmacogenomics of hyaluronic acid - Elena E. Vaiman; Natalia A. Shnayder; Anna V. Dyuzhakova; Evgenia I. Nikitina; Olga B. Borzykh; Regina F Nasyrova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Abstract.Introduction: Hyaluronic acid (hyaluronan, HA) has become the most popular tool for improving the skin condition during aging, correcting wrinkles and other cosmetic defects. Objective: Analysis of the results of studies that reflect the pharmacogenomics of the synthesis, degradation, and reception of HA. Materials and methods: We searched for full-text publications in Russian and English in the E-Library, PubMed, Springer, Clinical keys, Google Scholar databases, using keywords and combined word searches (hyaluronic acid, hyaluronan, synthesis, degradation, reception, receptor, genetics), over the past decade. In addition, the review included earlier publications of historical interest. Despite our comprehensive searches of these commonly used databases and search terms, it cannot be excluded that some publications may have been missed. Results: The lecture examines: the role of ha in normal and aging human; genes involved in the synthesis (HAS1, HAS2, HAS3), degradation (HYAL1, HYAL2, HYAL3) and reception of ha (CD44, HARE, RHAMM); as well as the expression of their encoded proteins and enzymes in the skin. Conclusion: Expanding our knowledge of the pharmacogenomics of endogenous ha and increasing the exogenous HA drugs (used in anti-aging therapy and medical cosmetology) on the pharmaceutical market requires taking into account individual, including genetically determined, characteristics of the body of each individual patient to ensure an optimal balance of effectiveness/safety of exogenous HA from the point of view of personalized medicine